Implementation of Baubau Mayor Regulation on Building Boundary Guidelines - Andi Tenri; Syahril Ramadhan; Wa Ode Indryah Widiah Wisti Yeti (Sean Institute, 2025)
The purpose of this study is to determine the Implementation of the Baubau Mayor's Regulation Policy on Boundary Line Guidelines in Baubau City. The research method is descriptive qualitative. Data collection techniques use observation, interview and documentation techniques. The data used are primary data and secondary data. Data analysis techniques include data reduction, data presentation and drawing conclusions. The study shows that the implementation of the Mayor's Regulation policy Number 56 of 2022 concerning boundary line guidelines in Baubau City has been implemented, although there are still some obstacles in the field. This can be seen from the Standards and Policy Targets that are clear and easy to understand will be implemented well and more regularly, planned, organized, Adequate resources help in implementing a policy properly, effectively, the character of the policy implementers must be tough and strict to make the community obey the applicable legal sanctions, communication of the policy implementers is quite good, the disposition of the policy implementers related to spatial planning is good but sometimes gets rejection on the grounds that the policy is not appropriate, the socio-cultural environment in the implementation according to the character of the community towards accepting policies from the government is more open.